The “Jack-of-all-Trades” Flagellum From Salmonella and E. coli Was Horizontally Acquired From an Ancestral β-Proteobacterium - Ferreira, Josie L.; Coleman, Izaak; Addison, Max L.; Zachs, Tobias; Quigley, Bonnie L.; Wuichet, Kristin; Beeby, Morgan (Frontiers in Microbiology, 2021)
The gamma-proteobacteria are a group of diverse bacteria including pathogenic Escherichia, Salmonella, Vibrio, and Pseudomonas species. The majority swim in liquids with polar, sodium-driven flagella and swarm on surfaces with lateral, non-chemotactic flagella. Notable exceptions are the enteric Enterobacteriaceae such as Salmonella and E. coli. Many of the well-studied Enterobacteriaceae are gut bacteria that both swim and swarm with the same proton-driven peritrichous flagella. How different flagella evolved in closely related lineages, however, has remained unclear. Here, we describe our phylogenetic finding that Enterobacteriaceae flagella are not native polar or lateral gamma-proteobacterial flagella, but were horizontally acquired from an ancestral beta-proteobacterium. Using electron cryo-tomography and subtomogram averaging, we confirmed that Enterobacteriaceae flagellar motors resemble contemporary beta-proteobacterial motors, and are distinct to the polar and lateral motors of other gamma-proteobacteria. Structural comparisons support a model in which gamma-proteobacterial motors have specialized, suggesting that acquisition of a beta-proteobacterial flagellum may have been beneficial as a general-purpose motor suitable for adjusting to diverse conditions. This acquisition may have played a role in the development of the enteric lifestyle.